Physicochemical Evaluation of the Oil Extracted from Anacardium occidentale Almonds for Energy Use - YETE, PELAGIE; TOGBE, Finagnon Crépin Alexis; YOVO, Franck (My University, 2020)
The present study aimed at exploring the potential of producing biofuels from unconventional vegetable oils extracted from Anacardium occidentale kernels. Accordingly, oils were extracted from Anacardium occidentale kernels and subjected to physical and chemical characterization namely: density; lower calorific value (PCI); quality indexes; fatty acid profile, viscosity using French and ISO standards. Results revealed that Anacardium occidentale almonds have a lipidic potential of 52.54%, the transesterification reaction yield was 78.28%. As for the quality indices of the vegetable oil: acidity (˃1%); saponification index (205.29 mg KOH/g-oil); peroxide value (8.08 meq O2/kg-oil) and iodine value (108.84 mg iodine/g-oil) were considerably reduced for biodiesel. The vegetable oil was unsaturated type with the predominance of oleic acid (43.86%). The fuel characteristics of the oil obtained were: acidity (2.89%), density at 40°C (0.796 g/cm3) cetane number (41.47). The raw extracted oil is not usable as fuel for engine due to its very high viscosity ranging 30.69 mm2/s. As a consequence, a prior chemical treatment is necessary to reduce the viscosity. Our results provided an insight on the energetic potential of the investigated oil, with respect to its use as a source for biodiesel in replacement of the current conventional diesel fuel.
Keywords: Anacardium occidentale; physico-chemical and thermodynamic parameters; fuel capacity.